2019
DOI: 10.1063/1.5092524
|View full text |Cite
|
Sign up to set email alerts
|

Strain deformation in GaAs/GaAsBi core-shell nanowire heterostructures

Abstract: We present the growth and strain deformation of sharp-facetted GaAs/GaAsBi core–shell heterostructure nanowires on a Si (111) substrate. The nanowires have a 90 nm wide GaAs core surrounded by an 80 nm thick GaAsBi shell. The sample was analyzed using microbeam synchrotron x-ray diffraction to resolve the local strain status at the GaAs/GaAsBi heterointerface. GaAsBi showed identical lattice constants for its vertical and lateral lattice planes. From the lattice constants, the Bi concentration in GaAsBi was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…19 However, there is rapidly growing research interest in this novel material system as demonstrated by the subsequent experimental studies in the last few years showing promising progress. [20][21][22][23][24][25][26] One of the critical challenges in the next few years will be to incorporate large Bi fractions in the active region of nanowire to achieve optical wavelengths to target photonic devices working in the near to mid and far infra-red regimes. For example as predicted in this work, the photonic devices aimed at the telecommunication applications would require Bi fractions in the range of 10 to 15%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 However, there is rapidly growing research interest in this novel material system as demonstrated by the subsequent experimental studies in the last few years showing promising progress. [20][21][22][23][24][25][26] One of the critical challenges in the next few years will be to incorporate large Bi fractions in the active region of nanowire to achieve optical wavelengths to target photonic devices working in the near to mid and far infra-red regimes. For example as predicted in this work, the photonic devices aimed at the telecommunication applications would require Bi fractions in the range of 10 to 15%.…”
Section: Discussionmentioning
confidence: 99%
“…11,[15][16][17][18] However, very recently, the focus has been shifted towards incorporating highly-mismatched bismuth containing GaAs materials such as GaBixAs1−x in the active region of core−shell nanowires. [19][20][21][22][23][24][25][26] The GaBixAs1−x materials which are formed by adding dilute concentration of bismuth (Bi) in the GaAs material offer unique electronic properties which are not readily accessible from traditional III-V alloys. It has been shown that the band-gap energy of the GaBixAs1−x material decreases dramatically with increasing Bi composition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic, not accessible in the conventional III-V materials, is unique for the bismide alloys and is expected to drastically suppress the non-radiative Auger recombination and the inter-valence band absorption (IVBA) processes in the bismide-based photonic devices, which otherwise plague the efficiency of the devices made up of the conventional semiconductor materials [28][29][30]. Therefore, the design of the GaBi x As 1−x /GaAs core−shell nanowires is an important emerging area of research with tremendous potential for the implementation of photonic devices with low internal losses and improved temperature stability [17][18][19].To enable the design of optoelectronic devices based on the semiconductor nanowires with optimised characteristics, it is of paramount importance to thoroughly understand the relationship between the physical attributes of a nanowire, such as its geometry and material composition, and the resulting electronic structure and optical transition strengths. An in-depth analysis of the nanowire properties can also provide a useful guidance for the future experiments to target optimised physical parameters during the fabrication stage.…”
mentioning
confidence: 99%
“…This characteristic, not accessible in the conventional III-V materials, is unique for the bismide alloys and is expected to drastically suppress the non-radiative Auger recombination and the inter-valence band absorption (IVBA) processes in the bismide-based photonic devices, which otherwise plague the efficiency of the devices made up of the conventional semiconductor materials [28][29][30]. Therefore, the design of the GaBi x As 1−x /GaAs core−shell nanowires is an important emerging area of research with tremendous potential for the implementation of photonic devices with low internal losses and improved temperature stability [17][18][19].…”
mentioning
confidence: 99%